Editorial - Clavijo, Amparo (Colombian Applied Linguistics Journal, 2011)
In our previous issue I highlighted the positive impact that classroom research has on the teacher, the context, the field, and on the creation of local knowledge in education. In this issue, I would like to refer to the value of narrative inquiry in education as a methodology for qualitative research and a resource for teacher professional development. Narrative construction is understood by qualitative researchers as a vital human activity that structures experience and gives it meaning (Kramp, 2004).